The labor market in Russia, 2000-2017 - Vladimir Gimpelson (IZA World of Labor, 2019)
Being the largest economy in the Eurasian region, Russia's labor market affects economic performance and well-being in several former Soviet countries. Over the period 2000–2017, the Russian labor market survived several deep crises and underwent substantial structural changes. Major shocks were absorbed largely via wage adjustments, while aggregate employment and unemployment showed little sensitivity. Workers have paid the price for this rather stable employment situation in the form of volatile wages and a high risk of low pay.
Keywords: P2; P3; E24; 330; education; human capital; transition economics; unemployment; earnings dynamics